Pengaruh penyuluhan menggunakan media audiovisual terhadap pengetahuan kelompok wanita tani dalam pemanfaatan pekarangan di Kecamatan Sigaluh Kabupaten Banjarnegara - Nunihartini, Yekti; Nurul Hidayat; Tyas Retno Wulan; Lilik Kartika Sari; Edi Santoso (Fakultas Pertanian Universitas Majalengka, 2024)
The purpose of the study was to determine the effect of extention using audiovisual media on the knowledge of kelompok wanita tani in utilizing yards in Sigaluh District Banjarnegara Regency. The research was implemented in July 2024. Involving 30 kelompok wanita tani from 15 villages with the number of samples in the intervention group 268 and control group 268. The results of the study were obtained with a good perception found in the amount of 191 (71.3%). Kelompok wanita tani knowledge in the intervention group was found to be mostly in the moderate category at 223 (83.2%) and knowledge after video intervention was found to be good knowledge at 242 (90.2%). While the knowledge of the control group was mostly in the category of less than 144 (53.7%) and knowledge after the intervention was found with sufficient knowledge as much as 240 (89.6%). There is a significant effect of extention using audiovisual media on the knowledge of kelompok wanita tani in the Sustainable Food Yard Program (P2L) in Sigaluh District, Banjarnegara Regency (p<0,05).